Ketidakadilan Gender dan Bentuk Perlawanan Tokoh Perempuan dalam Novel Malam Seribu Jahanam: Kajian Feminisme - Khofifah Rahmah; Kurnia Rachmawati; Dicky Rachmat Pauji (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines gender injustice and forms of resistance in Malam Seribu Jahanam by Intan Paramaditha using feminist literary criticism and Mansour Fakih’s framework of gender injustice. The research is motivated by the persistence of gender inequality in Indonesian society as reflected in literary works. It aims to identify forms of gender injustice and analyze how female characters respond to patriarchal domination. Unlike previous studies that primarily focus on women’s oppression, this research highlights the representation of gender minorities beyond the male–female binary, particularly trans women, who are marginalized through moral stigma, social exclusion, and rejection from religious and social spaces. This perspective broadens feminist literary analysis by incorporating a more inclusive understanding of gender injustice. The study employs a qualitative descriptive method through close reading and thematic categorization of data. The findings reveal that gender injustice appears in interconnected forms, including marginalization, subordination, stereotyping, violence, and unequal workloads. However, female characters are portrayed not merely as victims but as agents who negotiate identity, assert autonomy, and resist patriarchal control.